Small Lexemes, Large Semantics: Prepositions and Theology in the Golden Calf Episode (Exodus 32–34) - Timmer, Daniel C. (Biblica, 2007)
Despite the current methodological impasse with which OT studies continues to wrestle, this study shows that dynamic elements within the text can, somewhat surprisingly, contribute to the text’s coherence. The various prepositions and statements regarding divine presence in Exod 32–34 are fundamental to the development and integrity of the narrative as its stands. Further, the fact that this complex progression in divine presence spans pericopae usually attributed to various sources suggests that the various pericopae are more in harmony with one another than is often recognized. These conclusions call for renewed attention to the text of Exodus as it stands, both within the golden calf episode and more broadly.